Arch vessels' switch in frozen elephant trunk: a new technique to facilitate the second-stage endovascular thoraco-abdominal aorta repair. (29th December 2022) - Gatta, Emanuele; Berretta, Paolo; Vento, Vincenzo; Di Eusanio, Marco
: In patients with extensive thoraco-abdominal aortic disease, staged hybrid repair involving open total aortic arch replacement and endovascular thoraco-abdominal aorta repair with branched stent graft has emerged as a valuable treatment option. However, total arch replacement with the available branched vascular grafts often results in acute angulation between the reimplanted vessels and the aortic arch hampering antegrade catheterization of the thoraco-abdominal aorta during the second endovascular stage. Here, we present our 'switch technique' for arch vessels' reimplantation to facilitate antegrade aortic catheterization of the thoraco-abdominal aorta and visceral vessels. Abstract : Staged hybrid repair involving open total aortic arch replacement with classic/frozen elephant trunk (FET) and endovascular thoraco-abdominal aorta repair with branched stent graft (BEVAR) has emerged as a valuable option for the treatment of patients with extensive thoraco-abdominal aortic (TAA) pathologies.